AN IMPROVEMENT OF ARJUNA 1.0 CONVEYOR SYSTEM FOR 3D IRRADIATION - Saefurrochman, Saefurrochman; Purwanto, Agus Tri; Adabiah, Suhadah Rabi'atul; Sukaryono, Sukaryono; Setiaji, Galih; Arthanto, Dwi Handoko; Anggraeni, Karina; Rachmawati, Isti Dian; Dwiatmaja, Agus; Wijono, Wijono; Nuraini, Elin; Andriyanti, Wiwien; Darsono, Darsono; Adjie, Andreas Bimo Putro (GANENDRA Majalah IPTEK Nuklir, 2023)
An improved design of the conveyor system of Arjuna 1.0 electron accelerator for 3D object irradiation has been done. The penetration of low energy electrons is less than 1 cm in the surface, causing a challenge for the irradiation process for sterilization of 3D objects. We design a conveyor that can be rotated 360o to irradiate objects evenly. The dimension of this conveyor is 1750 x 600 x 800 mm and the maximum diameter of the object is 7 cm. Based on the Frame Bending Stress analysis to calculate the strength of the conveyor frame, it is shown that the maximum displacement is only 0.029 mm, which is very small so it will cause no disturbance to power transfer from the motor to the conveyor. The normal stress (Smax) is 3.926 MPa and the bending stress for Smax (Mx) and Smax (My), are 2.391 MPa and 3.925 MPa respectively. We also calculate the stress analysis of the 3 mm-thickness of the motor mount and found that the Von-Misses Stress, first, and third Principal Stress are 4.425 MPa, 5.01 MPa, and 1.95 MPa respectively. These results confirm that the design and the material used for the conveyor are safe because the stress is very low than the material’s yield strength which is 207 MPa. The power needed for this conveyor is 0.01724 kW, with a maximum speed is 880 rpm. The new model of 3D conveyor has been constructed and can be implemented to ARJUNA 1.0 to irradiate objects on all its surfaces